Acute effects of glucocorticoids on serum markers of osteoclasts, osteoblasts, and osteocytes - Brabnikova Maresova, Kristyna; Pavelka, Karel; Stepan, Jan J (Calcified tissue international, 2013)
The aim of this study was to investigate the acute effects of oral glucocorticoids in doses used in clinical practice on biochemical indices of the function of osteoclasts, osteoblasts, and osteocytes. In 17 adult patients suffering from various medical pathologies requiring systemic steroid therapy that were never before treated with glucocorticoids, glucocorticoid treatment was initiated (mean prednisolone equivalent dose of 23.1 ± 12.7 mg/day, range 10-50). Fasting morning serum concentrations of osteocalcin (OC), amino-terminal propeptide of type I procollagen (PINP), type 1 collagen cross-linked C-telopeptide (βCTX), soluble receptor activator of nuclear factor kappaB ligand (sRANKL), osteoprotegerin (OPG), sclerostin, Dickkopf-1 (Dkk-1), and high-sensitivity C-reactive protein (hsCRP) were measured at baseline and on three consecutive days. Significant reductions in serum OC, PINP, OPG, sclerostin, and hsCRP were observed during 96 h of glucocorticoid administration, while serum βCTX showed a significant percentual increase. A significant positive correlation was found between serum concentrations of Dkk-1 and βCTX after 96 h of treatment with glucocorticoids. A significant drop in serum sclerostin, OPG, and OC observed in this study may reflect the rapid glucocorticoid-induced apoptosis of osteocytes.
Keywords: Humans; Case-Control Studies; osteoprotegerin; Osteoprotegerin; osteokalcin; lidé středního věku; kolagen typu I; C-reaktivní protein; revmatické nemoci; studie případů a kontrol; Glucocorticoids; genetické markery; osteoblasty; Dose-Response Relationship, Drug; Aged; Female; adaptorové proteiny signální transdukční; dospělí; Osteocytes; Collagen Type I; senioři; lidé; osteoklasty; Adaptor Proteins, Signal Transducing; Biomarkers; Intercellular Signaling Peptides and Proteins; Osteoblasts; kostní morfogenetické proteiny; osteocyty; peptidy; Peptides; ligand RANK; Adult; Peptide Fragments; Rheumatic Diseases; biologické markery; ženské pohlaví; Bone Morphogenetic Proteins; mezibuněčné signální peptidy a proteiny; Male; Middle Aged; prokolagen; glukokortikoidy; Genetic Markers; Aged, 80 and over; peptidové fragmenty; Osteoclasts; RANK Ligand; senioři nad 80 let; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; prospektivní studie; Procollagen; C-Reactive Protein; Osteocalcin; Prospective Studies